GAMBARAN HASIL SITOLOGI SERVIKS WANITA PEKERJA SEKSUAL TIDAK LANGSUNG PADA HOTSPOT X KECAMATAN MARPOYAN DAMAI - Rahmadani, Fetty Try; Ade, Wiwit; Sofian, Amru (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCervical cancer is the second most frequent cancer in women in the world after breast cancer. Indirect female sex workers have high risk to get cervical cancer. The number of cervical cancer cases can be reduced with Pap smear screening. The purpose of this study was to know the result of cervical smear cytology examination toward indirect female sex workers at hotspot X Marpoyan Damai Pekanbaru. The method of this research is descriptive. The population of this study were all of indirect female sex workers at hotspot X Marpoyan Damai Pekanbaru and the samples were takwn with total sampling methode. The result showed that there were 33 Consist 6% diagnosed with negative intraepithelial lesion or malignancy (Bacterial vaginosis), 30% diagnosed with LSIL and 64% diagnosed with ASCUS. The conclusion is ASCUS was the most common intraepithelial lesion of cervical cancer on indirect female sex workers at hotspot X Kecamatan Marpoyan Damai Pekanbaru. Keywords:Cervical smear, Pap smear Cervical cancer, Indirect Female Sex Workers, Hotspot X Marpoyan Damai